Economic Mechanisms Ensuring the Right for Favourable Environment in the Legislation of the Russian Federation - Yalbulganov, Alexander (Pontificia Universidad Javeriana, 2013)
This article examines the financial guarantees to implement the citizenship constitutional right for a favorable environment in the Russian Federation (RF), the use of different environmental taxes for that purpose, along with a critical analysis of the Law’s rules and regulations and the legal stand point of the Constitutional Court regarding the legal nature of the costs charged by companies for their negative impact on the environment.